Fundamental Role of Macro and Microeconomics to Profitability and the Implications on Stock Return: Evidence from Banking Companies on the Indonesia Stock Exchange - Hakim, Luqman; Martono, Martono (International Journal of Economics and Financial Issues, 2019)
This study is intended to analyze the fundamental role of Macro and Micro on profitability which has implications for Stock Return in the banking industry on the Indonesia Stock Exchange. Macro and micro fundamentals in this study use Gross Domestic Product (GDP), Inflation (INF), Rupiah Exchange Rate against the US Dollar (Exchange Rate), CAR, Non Performing Loans (NPL), BOPO, LDR. The results of partial testing of independent variables that significantly influence ROA in the first research model are BOPO, LDR, PDB, KURS, INF, other variables are not significant. Tests together show that the independent variables significantly influence ROA. Of the 24 banking companies that became the study sample, the banking companies that had the greatest sensitivity influence were the SDRA bank (Bank Himpunan Saudara 1906, Tbk) and the banking company that had the smallest sensitivity effect was the BABP bank (Bank Bumiputera Indonesia, Tbk). Based on the formed R2, the independent variable is able to explain changes in the rise and fall of ROA of 24.05%. The results of the second model of the study showed that the NPL, INF and ROA variables significantly affected the stock returns of banking companies where the most dominant ROA variable and in testing together resulted that the variables of all independent variables significantly affected the stock returns of banking companies listed on the Exchange Indonesian effect. Of the 24 banking companies that became the study sample, the banking company that had the greatest sensitivity influence was the BABP bank (Bank Bumiputera Indonesia, Tbk). while the banking company that has the smallest sensitivity effect is the BNGA bank (Bank CIMB Niaga, Tbk). Based on the formed R2, the independent variable is able to explain changes in the rise and fall of stock returns by 53.35%. Keywords: Profitability, stock markets, banking, Indonesia JEL Classifications: E10, E32, E60 DOI: https://doi.org/10.32479/ijefi.8827